FINANCIAL LITERACY AND SME PERFORMANCE: A LITERATURE REVIEW OF INDONESIAN MICRO BUSINESSES - Desi Rahmawati; Latifatul Isro’iyah (CV. Lafadz Jaya, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in Indonesia's economic growth, but still face various challenges, especially in managing business finances. One of the factors that is considered to affect the success of the business is financial literacy. Financial literacy is not only related to the ability to understand financial concepts, but also the ability to make the right financial decisions to support business sustainability. This study aims to analyze the relationship between financial literacy and MSME performance through a literature review approach on micro enterprises in Indonesia. The method used in this study is literature review by reviewing various scientific articles, national and international journals, as well as relevant previous research on financial literacy and MSME performance. The results of the study show that financial literacy has a positive influence on the performance of MSMEs, especially in the aspects of capital management, business decision-making, financial efficiency, and the ability to deal with business risks. In addition, financial literacy also plays a role in improving the adaptability of MSMEs to technological developments and financial digitalization. This study found that most of the previous research still focused on quantitative empirical approaches, so that the review of the integrative literature is still limited. Therefore, this research is expected to make a theoretical contribution to the development of financial literacy studies and become a consideration for the government and business actors in improving the quality of MSME management in Indonesia.